Wound treatment and selective help in a termite-hunting ant. Issue 1872 (14th February 2018) - Frank, Erik T.; Wehrhahn, Marten; Linsenmair, K. Eduard
Abstract : Open wounds are a major health risk in animals, with species prone to injuries likely developing means to reduce these risks. We therefore analysed the behavioural response towards open wounds on the social and individual level in the termite group-hunting ant Megaponera analis . During termite raids, some ants get injured by termite soldiers (biting off extremities), after the fight injured ants get carried back to the nest by nest-mates. We observed treatment of the injury by nest-mates inside the nest through intense allogrooming at the wound. Lack of treatment increased mortality from 10% to 80% within 24 h, most likely due to infections. Wound clotting occurred extraordinarily fast in untreated injured individuals, within 10 min. Furthermore, heavily injured ants (loss of five extremities) were not rescued or treated; this was regulated not by the helper but by the unresponsiveness of the injured ant. Interestingly, lightly injured ants behaved 'more injured' near nest-mates. We show organized social wound treatment in insects through a multifaceted help system focused on injured individuals. This was not only limited to selective rescuing of lightly injured individuals by carrying them back (thus reducing predation risk), but, moreover, included a differentiated treatment inside the nest.